POS1153 PRELIMINARY EVALUATION OF THE SAFETY AND ANALGESIC EFFICACY OF THE TRPV1 AGONIST RTX-GRT7039 IN KNEE OSTEOARTHRITIS: A RANDOMISED, DOUBLE-BLIND, EXPLORATORY PHASE II STUDY - Ostenfeld, T.; Ivanavicius, S.; Stancik, R.; Conaghan, P. G. (Annals of the rheumatic diseases, 2024)
Background:RTX-GRT7039 (resiniferatoxin; RTX), is a potent and selective agonist of the transient receptor potential vanilloid 1 (TRPV1) being developed for treatment of pain related to knee osteoarthritis (KOA). RTX-mediated activation of TRPV1-expressing neurones is followed by reversible defunctionalisation of the peripheral terminals of C- and A-delta nerve fibres that can lead to prolonged analgesia.Objectives:The primary objective of this study (P03, Part 1) was to compare the analgesic effects of single intra-articular (IA) injections of RTX (0.5 mg and 2 mg; Euphorbia resinifera latex in the injectate solution) compared to placebo, at 3 and 6 months post-injection, in participants with chronic osteoarthritic (OA) knee joint pain. Secondary objectives were to evaluate the analgesic effects of RTX-GRT7039 versus placebo in terms of a responder analysis (percentage of subjects achieving ≥50% or ≥70% reduction in VAS pain score) and changes in WOMAC total and subscale scores (pain, physical function and stiffness). Safety and tolerability were also evaluated.Methods:The study was conducted as a randomized, double-blind, placebo-controlled, single-dose trial of RTX-GRT7039. Eligible patients were aged 40 to 80 years with radiographic knee OA (Kellgren-Lawrence Grade 2-4 in the last 3 years) and a baseline VAS (0-100 mm) pain score ≥40mm on motion in the target knee, with or without pain medication. 67 subjects were randomized to treatment with either RTX 0.5 mg (N=24) or 2 mg (N=23), or placebo (N=20), administered IA into the index knee. IA ropivacaine (5 mL, 0.5%) was administered 15 mins before investigational medicinal product (IMP). VAS scores were used to evaluate pain on motion as the average of the last 2 days in a target knee between baseline and at 3 and 6 months post injection.Results:Baseline demographic characteristics and OA pain scores were comparable across treatment groups. In the ITT population, a reduction in the VAS scores for pain on motion in the treated knee after IA injection was observed as early as the first trial visit post-injection (Day 8) with the effect lasting until the last trial visit (Month 6; Figure 1). Subjects receiving RTX reported a greater pain reduction than subjects receiving placebo. At the 3 months visit, there was a higher mean [SD] absolute reduction of VAS score (baseline corrected) in the RTX 0.5 mg group (37.43 [19.79]) and the 2 mg group (36.68 [34.16]) than in the placebo group (17.00 [23.09]). At 6 months, the mean (SD) absolute reduction of VAS score was 33.52 (22.89) in the RTX 0.5 mg group, 41.48 (32.57) in the 2 mg group, and 28.26 (25.02) in the placebo group. Consistent with these data, the RTX 0.5 mg and 2 mg treatment groups showed a greater reduction in WOMAC total and subscale scores (pain, physical function and stiffness) than the placebo group at both 3 and 6 months. The incidence of treatment emergent adverse events (TEAEs) in the RTX 2 mg group (78.3%) and placebo group (75.0%) were comparable, but lower in the RTX 0.5 mg group (62.5%). The most commonly reported TEAEs were arthralgia, back pain, nasopharyngitis and headache. The majority of TEAEs were mild and unrelated to IMP or ropivacaine. Seven SAEs were reported in 6 subjects [2 subjects (0.5 mg), 3 subjects (2 mg) 1 subject (placebo)], none of which were considered to be related to the IMP or ropivacaine. No safety concerns were raised based on other evaluated safety parameters. Injection site pain/procedural pain was expected after IA injection due to the mode of action of RTX-GRT7039 and was not recorded as a TEAE within 24 hours after IMP administration.Conclusion:This exploratory trial indicates that single IA doses of RTX (0.5 mg and 2 mg; Euphorbia resinifera latex in the injectate solution) have the potential to deliver meaningful pain relief for patients with knee OA. Analgesic onset occurred within one week of administration and was evident for at least 3 months during the follow-up period. Injection site pain was expected and transient. Overall, RTX-GRT7039 was found to have a good safety profile and to have been well tolerated.REFERENCES:NIL.Acknowledgements:NIL.Disclosure of Interests:Thor Ostenfeld Grunenthal, Stefan Ivanavicius Grunenthal, Roman STANCIK: None declared, Philip G. Conaghan AbbVie, Eli Lilly, Novartis, AbbVie, AstraZeneca, BMS, Eli Lilly, Galapagos, Genascence, GSK, Grunenthal, Janssen, Levicept, Moebius Medical, Novartis, Stryker, Takeda, TrialSpark